Speciation, Transformation, and Accumulation of Manure-derived Cu and Zn in the Soil–Rice System. Issue 1 (2nd January 2020) - Zhang, Wenyuan; Yu, Tianhong; Yang, Xu; Li, Huashou
ABSTRACT: Pig manure has been successfully utilized as organic fertilizer to field crops in China. In this study, we used the cement pool plot test to investigate the speciation change and bioavailability of Cu and Zn derived from different pig manures (the fresh pig manure [FM1], the composting pig manure [FM2], and the dry-fermentation-bed pig manure [FM3]) in a soil–rice system. Results showed that the soil pH and the carbon content increased after applying pig manures. Cu and Zn contents in soil also remarkably increased but maintained under the safety standards (except Cu content in FM3). The exchangeable and carbonate-associated Cu and Zn both decreased over time, whereas Cu and Zn in Fe-Mn oxide form and organic-bound state increased and were the dominating components in soil. The pig manures, especially FM2, improved the rice biomass and yield. However, FM3 caused high Cu and Zn accumulation in rice. Moreover, the Cu level in grain exceeded the Chinese food hygiene standard, but the Zn level remained under the safety concentration. Collectively, it is imperative to assess the potential risk of Cu and Zn originated from pig manures. Cu more easily exceeded the safety standard than Zn, although Zn levels can reach the limit concentration with continuous manure application.